Meningkatkan Kemampuan Pemecahan Masalah dan Komunikasi Matematis melalui Penerapan Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Sekolah Menengah Atas - Khairul Asri; M. Ikhsan; Marwan Marwan (Universitas Syiah Kuala, 2014)
The ability of mathematical problem solving and communication of high school students is still low, it is one of the main problems in mathematics education. Hence the need for the application of learning that can improve the ability of problem solving and mathematical communication students learning, one application of learning that can improve this ability is the application of learning in jigsaw Cooperative. This study aims to determine the increase in the problem solving and mathematical communication students as a whole or in groups. Another goal that you want to see in this study is to determine whether there is interaction between the application of learning and grouping students to increased problem solving skills and mathematical communication students; and the attitude of students towards learning Jigsaw cooperative. Popolation in this study were all students of class XI of SMAN 1 Bukit Bener Meriah by taking samples of the two classes (class experiment acquire contextual approach to learning and conventional learning gain control class) through purposive sampling of five parallel classes are available. This research is experimental and the instrument used is the type of the test (about problem solving and communication) and non-test (student attitude scale). Collecting data using test instruments such as problem solving and communication abilities as well as the mathematical scale questionnaire students' attitudes toward the implementation of cooperative learning jigsaw. To see the differences between the students' increased ability experimental group with the control group used the t-test with a significance level of 0.05 after testing prerequisites are met. The results showed that an increase in problem-solving and communication abilities of students receiving mathematical cooperative learning jigsaw better than students who received conventional learning. There is no interaction between the application of learning and ability grouping of students to an increase in mathematical problem solving and communication students. Based on the analysis of the student attitude scale showed a positive attitude towards learning with a contextual approach.